2018
DOI: 10.1007/s00382-018-4600-x
|View full text |Cite
|
Sign up to set email alerts
|

Linear trends in temperature extremes in China, with an emphasis on non-Gaussian and serially dependent characteristics

Abstract: Record-breaking hot and cold extremes have occurred in China in recent years and, therefore, it is compelling to investigate the long-term trend in temperature extremes at individual stations to see whether they have become more frequent. Many previous studies on the linear trend analysis of temperaure extremes in China have used oridinary least squares (OLS) regression, without consideration of non-Gaussian and/or serially dependent characteristics, or nonparametric methods, again not considering the latter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…The difference between them is statistically significant according to a two-sample Kolmogorov-Smirnov (K-S) test (p < 0.05). The K-S test is a non-parametric test, suitable for extreme indices which generally show non-Gaussian distribution characteristics 35,36 .
Figure 1The spatial pattern of annual-mean temperature ( a – c ) over China under stabilized 1.5 °C and 2 °C global warming relative to 2006–2015 (Units: °C). Dotted areas are statistically significant according to a two-sample Kolmogorov-Smirnov (K-S) test (p < 0.05).
…”
Section: Resultsmentioning
confidence: 99%
“…The difference between them is statistically significant according to a two-sample Kolmogorov-Smirnov (K-S) test (p < 0.05). The K-S test is a non-parametric test, suitable for extreme indices which generally show non-Gaussian distribution characteristics 35,36 .
Figure 1The spatial pattern of annual-mean temperature ( a – c ) over China under stabilized 1.5 °C and 2 °C global warming relative to 2006–2015 (Units: °C). Dotted areas are statistically significant according to a two-sample Kolmogorov-Smirnov (K-S) test (p < 0.05).
…”
Section: Resultsmentioning
confidence: 99%
“…The present studies on extreme temperature changes in mainland China show that although the most extreme high temperatures were increasing and extreme low temperatures were decreasing, there were certain differences between regions and magnitudes. It has been reported that days of extreme temperatures at some observatories in mainland China do not conform to a normal distribution (Qian et al 2019;Shen et al 2017;Zhang et al 2020;Xing et al 2020). Therefore, this difference may be related to the methods and data.…”
Section: Frost Days Cold Days and Warm Daysmentioning
confidence: 99%
“…In Brazil, these tests have been applied to identify significant changes in temperature (Ávila et al, 2014;Ferreira et al, 2015;Neves et al, 2016) and in rainfall (Ely and Dubreuil, 2017;Zilli et al, 2017). In the same way, worldwide studies were conducted to confirm changes in the weather variables mentioned previously (Chen and Zhai, 2017;Shi et al, 2018;Qian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%